Optical Considerations for Design of Surface Disinfection Devices Based on Uv-C Leds - Gramsch-Labra, E; Raff-Biggemann, U (SPIE, 2021)
Due to a serious pandemic scenario, the surface disinfection process using monochromatic light sources based on UV-C LEDs is becoming more and more required. A brief review of the optoelectronics parameters of the devices based on UV-C LEDs light sources and the UV-C dose required to achieve a 99,9% of inactivation on surfaces (3 log reduction) of human Coronavirus (HCov-OC43 used as SARS-CoV-2 surrogate) has been prepared. A new parameter labeled as "homogeneity factor"has been defined to be applied on a bounded area where the homogeneity of the distribution requires a reliable average dose. © COPYRIGHT SPIE. Downloading of the abstract is permitted for personal use only.